Analisis Kecemasan dalam Penentuan Jenjang Karier Siswa SMP - Sholikah, Siti Marifatus; Rohmah, Silfia Ainur; Asri, Dahlia Novarianing (Jurnal Bimbingan dan Konseling Ar-Rahman, 2025)
Anxiety that is often experienced by Junior High School (SMP) students is when faced with the process of determining career levels. This anxiety is closely related to the uncertainty of choices, environmental pressure, and the level of enthusiasm in facing competition. This study aims to obtain a description of junior high school students' anxiety in determining career levels. This study uses a qualitative approach with a phenomenological study. The data collection technique was carried out through structured interviews with five junior high school students to determine their anxiety in deciding their career path in terms of (1) uncertainty regarding future choices; (2) the form of enthusiasm for competition, and (3) pressure from the environment. The study results showed that students experienced anxiety in the uncertainty of future choices caused by the lack of exploration of self-potential, while pressure from the environment, such as family support or social experience, also influenced students' self-confidence levels. Negative anxiety can reduce learning motivation and make students hesitate in determining career choices that suit their abilities and interests. On the other hand, positive anxiety can be a motivation to study harder. For further research, Guidance and Counseling teachers need to provide adequate guidance for junior high school students so that they can recognize their potential, overcome emotional stress, and make the right decisions regarding further education paths. __________________________________________________________________Kecemasan yang seringkali dialami siswa Sekolah Menengah Pertama (SMP) adalah ketika dihadapkan pada proses menentukan jenjang karier. Kecemasan ini berhubungan erat dengan ketidakpastian pilihan, tekanan lingkungan, serta tingkat semangat menghadapi kompetisi. Penelitian ini bertujuan untuk memperoleh deskripsi kecemasan siswa SMP dalam menentukan jenjang karier. Penelitian ini menggunakan pendekatan kualitatif dengan studi fenomenologi. Teknik pengumpulan data dilakukan melalui wawancara terstruktur terhadap lima siswa SMP untuk mengetahui kecemasan dalam menentukan jenjang karier ditinjau dari (1) ketidakpastian terhadap pilihan masa depan; (2) bentuk rasa semangat terhadap kompetisi, dan (3) tekanan dari lingkungan. Hasil penelitian menunjukkan bahwa siswa mengalami kecemasan dalam ketidakpastian pilihan masa depan yang disebabkan kurangnya eksplorasi potensi diri, sementara tekanan dari lingkungan, seperti dukungan keluarga atau pengalaman sosial, turut mempengaruhi tingkat kepercayaan diri siswa. Kecemasan yang bersifat negatif dapat menurunkan motivasi belajar dan membuat siswa ragu dalam menentukan pilihan karier yang sesuai dengan kemampuan dan minat mereka. Sebaliknya, kecemasan yang bersifat positif dapat menjadi motivasi untuk lebih giat belajar. Bagi penelitian selanjutnya, guru Bimbingan dan Konseling perlu memberikan pendampingan yang memadai bagi siswa SMP agar dapat mengenali potensi diri, mengatasi tekanan emosional, dan membuat keputusan yang tepat terkait jalur pendidikan lanjutan.